Development of a model of contact shoe brake-drum interaction in the context of a mine hoisting machine - Zabolotnyi, K.; Zhupiiev, O.; Molodchenko, A. (Розробка родовищ, 2017)
Purpose. To develop models of contact brake shoe-drum interaction of a mine hoisting machine while braking, taking into account final bending stiffness of a beam and the effect of friction forces on the distribution of a contact pressure in it to make recommendations as for the rational design of a brake beam. Findings. Areas to apply the hypotheses on absolute stiffness of a beam and the non-effect of friction forces on the distribution of contact pressure in it while calculating force of brakes of mine hoisting machines have been analyzed. Physical and mathematical models of contact interaction between a brake beam of a mine hoisting machine and a drum in the braking process have been developed. Мета. Розробка моделі контактної взаємодії колодкового гальма шахтної підйомної машини з барабаном при гальмуванні з урахуванням кінцевої згинальної жорсткості балки та впливу сил тертя на розподіл контактного тиску задля створення рекомендацій до проектування раціональної конструкції гальмівної балки. Результати. Досліджено можливості застосування в силовому розрахунку гальм шахтних підйомних машин гіпотез щодо абсолютної жорсткості балки та відсутності впливу сил тертя на розподіл контактного тиску. Розроблені фізична і математична моделі контактної взаємодії гальмівної балки шахтної підйомної машини з барабаном у процесі гальмування. Цель. Разработка модели контактного взаимодействия колодочного тормоза шахтной подъемной машины с барабаном при торможении с учетом конечной изгибной жесткости балки и влияния сил трения на распределение в ней контактного давления для создания рекомендаций к проектированию рациональной конструкции тормозной балки. Результаты. Исследованы границы применения в силовом расчете тормозов шахтных подъемных машин гипотез об абсолютной жесткости балки и невлиянии сил трения на распределение в ней контактного давления. Разработаны физическая и математическая модели контактного взаимодействия тормозной балки шахтной подъемной машины с барабаном в процессе торможения.